Sincerity And Love In Alexandre Dumas Jr's The Lady Of The Camellias (1902): A Psychoanalytic Approach - Cahyani, Tami Nur, Dr. Phil. Dewi Chandraningrum, S. Pd, M. Ed, Titis Setyabudi, S.Si, M.Hum (2013)
The major problem in this study is how the major character proves her sincerity and love in The Lady of the Camellias (1902) novel by Alexandre Dumas Jr. This study focused on one of the major characters namely Marguerite Gautier, using the mean of structural element and psychoanalytic analysis. The object of this study is Alexandre Dumas Jr's The Lady of the Camellias novel published in 1902 by Werner. The type of this study is descriptive qualitative. The primary data source is the novel The Lady of the Camellias itself and the secondary data source is books or any information related to the practice of sincerity and love that support the psychoanalytic approach by Sigmund Freud. The technique of analyzing data in this research paper is descriptive. The result of the study comes to the three following conclusions. First, based on structural element in The Lady of the Camellias, it shows that character and characterization, setting, plot, point of view, style, and theme are related to each other and form of unity. Second, based on psychoanalytic analysis, the id, superego, and ego are reflected in each of major character's life. Third, the theory of sincerity, and theory of love are the individual emotion in human's life. It shows that the emotion faced by the major character Marguerite Gautier causes the conflict of her mental condition.